2012
DOI: 10.1179/102453312x13336169156933
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in multiple myeloma (MM)

Abstract: Thrombosis is a frequent feature in individuals with myeloma, particularly those treated with oral immunomodulatory drugs (IMID) such as thalidomide or lenalidomide concomitantly with anthracyclines or dexamethasone. Up to a third of these individuals may develop venous thrombosis if not given the benefit of prophylaxis. Interestingly, in contrast to individuals with solid tumors in whom thrombosis is a marker of poor prognosis, thrombosis does not impact overall survival in patients with myeloma. This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…For instance, dasatinib rarely induces pleural effusions or pulmonary hypertension, although the vascular issues noted with nilotinib are completely different and likely represent progressive atherosclerosis . In addition, combination therapies used in myeloma may increase the risk of venous and arterial thrombotic events . Overall, it is fair to say that these myriad vascular complications are important and ultimately require specific strategies to manage them effectively.…”
Section: Common CV Adverse Eventsmentioning
confidence: 99%
“…For instance, dasatinib rarely induces pleural effusions or pulmonary hypertension, although the vascular issues noted with nilotinib are completely different and likely represent progressive atherosclerosis . In addition, combination therapies used in myeloma may increase the risk of venous and arterial thrombotic events . Overall, it is fair to say that these myriad vascular complications are important and ultimately require specific strategies to manage them effectively.…”
Section: Common CV Adverse Eventsmentioning
confidence: 99%
“…The extraordinary advances in the therapeutic armamentarium available for patients with a new diagnosis of multiple myeloma or relapsed/recurrent disease has led to significant increases in overall survival (OS) but has also drawn attention to the management of treatment-related complications for these patients. Among the commonest complications seen in this population is venous thromboembolism (VTE), as more than 10% will develop VTE during the course of their disease [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…4,5,9,10,14 Thrombosis, for example, can be observed in all stages of MM but there is an increased risk with immunomodulatory drugs when combined with dexamethasone, as well as with the combination of melphalan and prednisone. 15 Additionally, immune-mediated inflammatory diseases are associated with myelosuppression. 9,[16][17][18] Bortezomib is commonly associated with gastrointestinal (GI) adverse events (AEs), reactivation of herpes zoster, bone marrow sup- [19][20][21] Thalidomide is even more strongly implicated in PN, 22 and a recent analysis of patients with newly diagnosed MM revealed that although thalidomide improved efficacy when added to melphalan-prednisone, it negatively impacted safety.…”
Section: Introductionmentioning
confidence: 99%